Spinal Cord Motion: Influence of Respiration and Cardiac Cycle - Winklhofer, S.; Schoth, F.; Stolzmann, P.; Krings, T.; Mull, M.; Wiesmann, M.; Stracke, C. P. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: To assess physiological spinal cord motion during the cardiac cycle compared with the influence of respiration based on magnetic resonance imaging (MRI) measurements.Materials and Methods: Anterior-posterior spinal cord motion within the spinal canal was assessed in 16 healthy volunteers (median age, 25 years) by cardiac-triggered and cardiac-gated gradient echo pulse sequence MRI. Image acquisition was performed during breath-holding, normal breathing, and forced breathing. Normal spinal cord motion values were computed using descriptive statistics. Breathing-dependent differences were assessed using the Wilcoxon signed-rank test and compared with the cardiac-based cord motion.Results: A normal value table was set up for the spinal cord motion of each vertebral cervico-thoracic-lumbar segment. Significant differences in cord motion were found between cardiac-based motion while breath-holding and the two breathing modalities (P < 0.01 each). Spinal cord motion was found to be highest during forced breathing, with a maximum in the lower cervical spinal segments (C5; mean, 2.1 mm ± 1.17). Image acquisition during breath-holding revealed the lowest motion.Conclusion: MRI permits the demonstration and evaluation of cardiac and respiration-dependent spinal cord motion within the spinal canal from the cervical to lumbar segments. Breathing conditions have a considerably greater impact than cardiac activity on spinal cord motion.Key points:• Cardiac-triggered and ECG-gated MRI allows for demonstration of the smallest spinal cord motions.• Respiratory influences seem to have the highest impact on spine motion.• In contrast, the influence of the cardiac cycle seems to be small.• The smallest spinal cord motions were measured during breath-hold.Citation Format:• Winklhofer S, Schoth F, Stolzmann P et al. Spinal Cord Motion: Influence of Respiration and Cardiac Cycle. Fortschr Röntgenstr 2014; 186: 1016 – 1021
Keywords: spinal cord; MR imaging; CNS